PHYSICOCHEMICAL ANALYSIS OF HONEYS PURCHASED IN CUIABÁ, MATO GROSSO – BRAZIL - Amorim, Mirelly dos Santos; ALMEIDA, MONIQUE RAFAELLA; SANTOS, JESSIKA ALESSANDRA DOS; OLIVEIRA, LIZANDRA CARLA PEREIRA DE; SIQUEIRA, NÁGELA FARIAS MAGAVE PICANÇO; FARIA, ROZILAINE APARECIDA PELEGRINE GOMES DE (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2021)
The objective of this study was to determine the physicochemical characteristics of honeys sold in supermarkets of Cuiabá – MT. The physicochemical analyzes were ashes, moisture, proteins, total sugars, reducing sugars, apparent sucrose, pH, acidity, electrical conductivity, water activity, soluble solids (°Brix), hydroxymethylfurfural (HMF) and color. The results were analyzed statistically using ANOVA and followed by a Tukey’s test at 5% of significance. The results were compared with the values allowed by current Brazilian legislation and the literature that verified honeys in other regions of the country. All the analyzed samples were within the legal parameters for moisture, ashes and acidity, however in the case of apparent sucrose all presented results were out of recommended. In the analyzes of proteins, total sugars, pH, electrical conductivity, Aw, soluble solids and HMF (qualitative) there are no Brazilian standards to determine the quality of honeys. Therefore, was concluded that it is important to implement complete parameters to assist the PIQ (Identity and Quality Standard) and the characterization of honeys produced in the most diverse locations, biomes and environmental conditions in Brazil.